Gastrointestinal and external parasites of the white-crested elaenia Elaenia albiceps chilensis (Aves, Tyrannidae) in Chile - Fuentes, Danny (2015)
The objective of this study is to evaluate the ectoparasites and helminths of the white-crested elaenia, Elaenia albiceps chilensis. Feather mites Anisophyllodes elaeniae, Trouessartia elaeniae, and Analges sp. were detected in 51% of birds(n=106), whereas 24% were infected with lice (Tyranniphilopterus delicatulus, Menacanthus cfr. distinctus, and Ricinus cfr. invadens). Helminths Viguiera sp. and Capillaria sp. were found in five of the birds that were necropsied (n=20). With the exception of A. elaeniae, T. elaeniae, and T. delicatulus, all parasites represented new records found for the white-crested elaenia, and therefore for the Chilean repertoire of biodiversity.